Fibrinogen may mediate the association between long sleep duration and coronary heart disease. (6th December 2012) - Hale, Lauren; Parente, Victoria; Dowd, Jennifer Beam; Sands, Megan; Berger, Jeffrey S.; Song, Yiqing; Martin, Lisa W.; Allison, Matthew A.
Summary Long sleep duration has been associated with increased risk of cardiovascular disease (CVD) and all‐cause mortality. Inflammation and coagulation have been hypothesized as possible physiological pathways to explain this association, although specific biomarkers have not been studied. Using longitudinal data from 3942 postmenopausal women in the Women's Health Initiative observational study and clinical trials, we investigated whether fibrinogen, an acute‐phase inflammatory protein involved in blood clotting, mediates the associations between sleep duration and coronary heart disease (CHD) and mortality among women. Fibrinogen levels were associated positively with self‐reported long sleep duration (9+ h per night), CHD and all‐cause mortality, even after adjustment for a range of sociodemographic characteristics, cardiovascular risk factors and comorbidities.Compared with self‐reported 7–8 h per night sleep duration, self‐reported long sleep duration was associated with increased odds of CHD [odds ratio (OR) = 2.05, 95% confidence interval (CI): 1.02–4.11]. Adjustment for fibrinogen levels reduced the increased odds of CHD associated with long sleep by approximately 8 percentage points (OR = 1.97, 95% CI: 0.98–3.97). A similar reduction in the OR was observed with mortality. For both outcomes there is support for partial mediation of 6–7%, suggesting that fibrinogen may be a mechanism through which long sleep duration is associated with CHD and mortality.